The role of cultural heritage in resilience planning: evidence from 100 Resilient Cities - Deniz Altay-Kaya; Damla Yeşilbağ (Techne)
As a container of accumulated experiences, cultural heritage connects past, present and future by transmitting knowledge to future generations through tangible/intangible assets. With this potential, cultural heritage can significantly contribute to community resilience, yet available resilience strategy documents place limited emphasis on cultural heritage. Based on this observed lack of systematic consideration, this paper analyses the resilience strategy documents presented in the 100 Resilient Cities Programme, and discerns six approaches towards cultural heritage, namely ignorance, economic development tool, identity construction, social component, physical integration tool, and comprehensive consideration. The paper discusses further ways cultural heritage can enhance community resilience.